The Importance of Tutors in Student Life - Dilbarkhon, Kholjigitova; Murodilla, Khaydarov (European Journal of Life Safety and Stability (2660-9630), 2021)
This article is a small research on the role of tutors in the University, the role of students in their lives and their spiritual and spiritual development. The main purpose is to identify the main activities of tutors at the University. Existing research, predominantly with lecturers, highlights that these relationships have academic and affective dimensions. Studies demonstrate good increase student motivation, engagement, and learning. The current study adds a student voice to this topic, focussing on their views of tutoring staff, who undertake much of the face-to-face teaching in universities.